Genetic predisposition and evolutionary traces of pediatric cancer risk: a prospective 5-year population-based genome sequencing study of children with CNS tumors. Issue 4 (6th April 2023) - Stoltze, Ulrik Kristoffer; Foss-Skiftesvik, Jon; van Overeem Hansen, Thomas; Byrjalsen, Anna; Sehested, Astrid; Scheie, David; Stamm Mikkelsen, Torben; Rasmussen, Simon; Bak, Mads; Okkels, Henrik; Thude Callesen, Michael; Skjøth-Rasmussen, Jane; et al.
Abstract: Background: The etiology of central nervous system (CNS) tumors in children is largely unknown and population-based studies of genetic predisposition are lacking. Methods: In this prospective, population-based study, we performed germline whole-genome sequencing in 128 children with CNS tumors, supplemented by a systematic pedigree analysis covering 3543 close relatives. Results: Thirteen children (10%) harbored pathogenic variants in known cancer genes. These children were more likely to have medulloblastoma (OR 5.9, CI 1.6–21.2) and develop metasynchronous CNS tumors ( P = 0.01). Similar carrier frequencies were seen among children with low-grade glioma (12.8%) and high-grade tumors (12.2%). Next, considering the high mortality of childhood CNS tumors throughout most of human evolution, we explored known pediatric-onset cancer genes, showing that they are more evolutionarily constrained than genes associated with risk of adult-onset malignancies ( P = 5e−4) and all other genes ( P = 5e−17). Based on this observation, we expanded our analysis to 2986 genes exhibiting high evolutionary constraint in 141, 456 humans. This analysis identified eight directly causative loss-of-functions variants, and showed a dose-response association between degree of constraint and likelihood of pathogenicity—raising the question of the role of other highly constrained gene alterations detected. Conclusions: Approximately 10% of pediatric CNS tumors can be attributed to rare variants in known cancer genes. Genes associated with high risk of childhood cancer show evolutionary evidence of constraint.